2021
DOI: 10.1155/2021/5567732
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Psychological and Behavioral Changes between Children following School Closure due to COVID-19

Abstract: School closure due to coronavirus disease 2019 (COVID-19) pushed children across ages and nationalities into a state of mental health crisis. In Japan, children between the ages of 6 and 18 were ordered to stay at home and observe social distancing for several months. This study is aimed at investigating the effects of quarantine due to COVID-19 on children belonging to different developmental stages in life. Data were collected from mothers of typically developing children aged between 6 and 18 years. The dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…After deduplication, we assessed 24,926 abstracts for eligibility (see Figure 1). After the screening process, 191 studies were included in the systematic review 50,51,56–244 with a total...…”
Section: Resultsmentioning
confidence: 99%
“…After deduplication, we assessed 24,926 abstracts for eligibility (see Figure 1). After the screening process, 191 studies were included in the systematic review 50,51,56–244 with a total...…”
Section: Resultsmentioning
confidence: 99%
“…Ueda et al reported about half of children, participated in the research, experienced sleep pattern change during the period and its change was predicted by a high level of depression (11). In Nakachi et al study, change tendency in sleep pattern was also observed in junior and high school students (12). Psychological problems were observed in lower grade of elementary school; they easily cried and complained, were unable to keep calm, and were dependent on parents and family members.…”
Section: "Stay At Home" Campaignmentioning
confidence: 88%
“…Desfechos secundários de saúdeO aumento do uso de telas foi igualmente preocupante[27, 32, 42, 55, 56, 62,63,[71][72][73][74][75], em alguns casos podendo se relacionar a um aumento de agressividade [62, 71], problemas de conduta [26, 28, 30, 32] e problemas psicológicos[76].Em um estudo com 514 crianças, o tempo de videogame correlacionou-se significativamente com maiores sintomas de desatenção, hiperatividade, problemas emocionais e de conduta[27]. Ademais, foram frequentes alterações de sono[36,38,48, 55,60, 62,65,66,[77][78][79][80][81], dos hábitos alimentares [55,78,79], aumento de peso[82,83] e diminuição de atividade física[42, 55, 62,65,73,79,84].…”
unclassified